Remission of obsessive-compulsive disorder using ketogenic metabolic therapy in support of exposure and response prevention: a retrospective case report - Nicole Laurent; Katherine A. Tague (Frontiers in Psychiatry)
BackgroundObsessive-compulsive disorder (OCD) is a chronic and disabling condition that frequently resists standard interventions, including SSRIs and Exposure and Response Prevention (ERP). This case study explores the adjunctive use of ketogenic metabolic therapy (KMT) in conjunction with ERP for a 26-year-old man with treatment-resistant OCD characterized by the symmetry/ordering symptom dimension. The patient achieved remission of OCD symptoms and sustained improvements in mood, emotional regulation, and quality of life.MethodsA 26-year-old male with treatment-resistant OCD self-treated with a modified ketogenic diet and psychotherapy assisted ERP over 12 weeks. The diet featured a 1.5:1 macronutrient ratio (fat:protein+carbohydrates), self-monitored for nutritional ketosis (ketone levels ≥0.8 mmol/L), and included daily symptom tracking. ERP targeted symmetry/ordering-related compulsions. Symptom severity was assessed using the Dimensional Obsessive-Compulsive Scale (DOCS) and the Depression Anxiety Stress Scales (DASS-21). Long-term outcomes were evaluated over a 95-week follow-up.ResultsWithin three weeks of initiating KMT and subsequent ERP, daily compulsive behaviors decreased from 3–8 hours to less than one hour. Significant reductions in DOCS symmetry/ordering subscale scores were sustained at 95 weeks. Concurrent improvements were observed in emotional distress, measured by DASS-21, with all subscale scores normalizing by week 7. Qualitative feedback highlighted enhanced emotional regulation, sleep quality, and ERP engagement, attributed to the ketogenic diet.ConclusionThis case demonstrates rapid and sustained remission of OCD symptoms with the use of KMT and ERP. The findings suggest that KMT may provide a metabolic foundation that enhances the efficacy of ERP. Further research is warranted to explore the potential role of KMT in treatment-resistant OCD.